Adjectives in Hypotaxis: Proposed Dimensions for a Description of Syntagms in Modern Written Arabic - Michalski, Marcin (Lingua Posnaniensis, 2010)
The purpose of this paper is to propose dimensions enabling a systematic description of biconstituent hypotactic adjectival syntagms in Modern Written Arabic. A dimension is conceived of as a set of homegeneous properties characterizing syntagms. A biconstituent hypotactic adjectival syntagm is a complex lingual sign constituted by two words that are bound by the relation of qualifi cation; “adjectival” means that at least one of these words is an adjective. Adjectives are identifi ed as a separate part of speech on the grounds of their attributive capability and concord with the qualifi ed substantive. Nine dimensions are proposed that make it possible to characterize syntagms with regard to properties of their adjectival constituent, morphological indicators of qualification, linear properties, syntactic function of their constituents and reducibility of a syntagm to its qualificatum. The dimensions and properties they contain can be used for conducting a characterization of any biconstituent hypotactic adjectival syntagm, i.e. determining a set of nine properties it shows with regard to all nine dimensions.